2012
DOI: 10.1002/14651858.cd004398.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Printed educational materials: effects on professional practice and healthcare outcomes

Abstract: The results of this review suggest that when used alone and compared to no intervention, PEMs may have a small beneficial effect on professional practice outcomes. There is insufficient information to reliably estimate the effect of PEMs on patient outcomes, and clinical significance of the observed effect sizes is not known. The effectiveness of PEMs compared to other interventions, or of PEMs as part of a multifaceted intervention, is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
221
3
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 436 publications
(255 citation statements)
references
References 129 publications
13
221
3
7
Order By: Relevance
“…However, guidelines in themselves cannot be assumed to change practice and public and professional education is also needed (Villar et al, 2001;Al-Almaie and Al-Baghli, 2004;Giguère et al, 2012). So, a plan of action is needed to encourage the implementation of practices that medical evidence confirms will benefit both mothers and their newborn, and to eliminate practices that are unnecessary and likely to be uncomfortable for women in Jeddah and elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…However, guidelines in themselves cannot be assumed to change practice and public and professional education is also needed (Villar et al, 2001;Al-Almaie and Al-Baghli, 2004;Giguère et al, 2012). So, a plan of action is needed to encourage the implementation of practices that medical evidence confirms will benefit both mothers and their newborn, and to eliminate practices that are unnecessary and likely to be uncomfortable for women in Jeddah and elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…43 Furthermore, printed education materials have a small beneficial effect on practice outcomes. 22 Our study was one-dimensional (using one style of education), and previous studies showed that multimethod, multiphased CPD has potential for the greatest impact on practitioner behavior. 44,45 CONCLUSION Continuing professional development education was an easily accessible method for delivering education to pharmacists on the use of the DBI for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…21 In contrast, printed educational material may have a small beneficial effect on professional practice outcomes, though little is known about its impact on patient outcomes or behavioral change. 22 Targeted educational interventions improve evidence-based practice skills and knowledge. 23 An interventional study using CPD education to investigate pharmacists' knowledge and application of the DBI as a clinical risk assessment tool in older adults has not been conducted previously.…”
Section: Introductionmentioning
confidence: 99%
“…For ISTs directed at professionals: The change in adherence for the ISTs is taken from the literature, specifically from Cochrane reviews, a randomized controlled trial, and a meta-analysis [36][37][38][39][40][41][42][43][44] . These included different kinds of health professionals and interventions, as data specifically for exercise and cancer survivors was not available.…”
Section: Discussionmentioning
confidence: 99%
“…It therefore remains unknown which interventions are most effective for particular cancer survivor subgroups 38 . Moreover, the generalisability of study results in many cases is limited as the patient samples often are not representative for the general group of cancer survivors since they mostly include women with breast cancer 39 . In addition, hardly any evidence exists on the long-term outcomes of cancer rehabilitation 18,40,41 .…”
Section: Cancer Rehabilitationmentioning
confidence: 99%